Design of a WSN for monitoring CO2 in the air and noise levels in Loja (MASKAY, 2019)
This article describes the design of a wireless network of sensors for monitoring CO2 in the air and noise levels developed for the urban area of the city of Loja. The procedure starts by analyzing the functionality, protocols, and characteristics of the Wireless Sensor Networks (WSN) and the implementation of Zigbee communication technology. Then, the monitoring scenario was determined for the network design through the city's more significant concentration of socio-economic activity. From these scenarios, the sectorization of the city center was preceded, establishing the primary sources of CO2 emission and noise levels. Then, the simulation was carried out using the Riverbed Modeler software to determine the evaluation parameters, such as the transmission speed, the delay, and the packets received from the chosen technology. Also, the sensor nodes and the coordinating node were designed to allow the establishment and communication of the network through the XBee PRO S2B module of the Zigbee technology. Finally, to evaluate the designed network, two types of tests were performed: a reception power level test and a validation test of the operation of the network based on the construction and implementation of prototypes of the proposed sensors, a node coordinator, and two sensor nodes (one node for CO2 monitoring and one for noise). The generated information is displayed in a graphical interface developed in the VS Express 2017 software.
Keywords: Zigbee; WSN; CO2; Xbee PRO; Wireless Networks; Sensors